Electronic Health Records in Ophthalmology: Source and Method of Documentation - Henriksen, Bradley S.; Goldstein, Isaac H.; Rule, Adam; Huang, Abigail E.; Dusek, Haley; Igelman, Austin; Chiang, Michael F.; Hribar, Michelle R. (American journal of ophthalmology, 2020)
This study analyzed and quantified the sources of electronic health record (EHR) text documentation in ophthalmology progress notes. EHR documentation review and analysis. Setting: a single academic ophthalmology department. Study population: a cohort study conducted between November 1, 2016, and December 31, 2018, using secondary EHR data and a follow-up manual review of a random samples. The cohort study included 123,274 progress notes documented by 42 attending providers. These notes were for patients with the 5 most common primary International Statistical Classification of Diseases and Related Health Problems, version 10, parent codes for each provider. For the manual review, 120 notes from 8 providers were randomly sampled. Main outcome measurements were characters or number of words in each note categorized by attribution source, author type, and time of creation. Imported text entries made up the majority of text in new and return patients, 2,978 characters (77%) and 3,612 characters (91%). Support staff members authored substantial portions of notes; 3,024 characters (68%) of new patient notes, 3,953 characters (83%) of return patient notes. Finally, providers completed large amounts of documentation after clinical visits: 135 words (35%) of new patient notes, 102 words (27%) of return patient notes. EHR documentation consists largely of imported text, is often authored by support staff, and is often written after the end of a visit. These findings raise questions about documentation accuracy and utility and may have implications for quality of care and patient-provider relationships.